Avaliação da qualidade seminal em adultos após uso de spirulina platensis e resveratrol - Verzeletti, Franciele Bona (2012)
Male infertility may be caused by different factors. The most common ones include the insufficient number of sperm and/or this little motility. The use of antioxidants should be contribute to the treatment of male infertility in patients with loss of seminal quality. The main objective of this study was evaluating if the of antioxidants (Spirulina platensis and resveratrol) contributes in the seminal quality among men between 40 and 60 years old. This is a randomized clinical study with two groups: Spirulina platensis (Sp) and Resveratrol (R), each of the groups has been compound by 25 men between 40 and 60 years old, wich means they were 50 in total. For the analysis, the Sp group were made to have 4 g of Spirulina platensis whereas the R group took 500 mg of Resveratrol, in both cases the medicine was taken in capsules and during 90 days. The sample was sent to spermogram analysis, before and after the therapy. All the men have been submitted to a standard questionnaire. The analysis of semen concentration achieved significance (p = 0,022) and morphology (p = 0,037) using Sp. Motility (p = 0,027) and vitality (p = 0,017) have significance with use R. It has been concluded that the terapy use has improving the seminal quality in men between 40 and 60 years old.